Laffer Curve and Taxable Revenue Elasticity: The Impact of Tax Deductions on a Dynamic General Equilibrium Model - Nahid Gohartash; Rouhollah shahnazi; Ahmad Sadraei javaheri; Mahboubeh Jafari; Parviz Rostamzadeh (پژوهشهای اقتصادی)
Aim and Introduction Making changes in the tax system is one of the basic and important needs for increasing government tax revenues. To achieve this, the tax system must move in a direction that increases the tax base. One of the most important solutions can be reducing tax exemptions and deductions. Since tax deduction plays an important role in determining tax revenues, ignoring its effect in tax studies can lead to misleading results. To address this research gap, this study uses a three-part dynamic general equilibrium model to estimate the Laffer Curve and investigate the effects of tax deductions on the curve and taxable income. Findings The analysis focuses on the household, business, and government sectors, highlighting the significance of tax deductions within each. Findings from this research show that, in the absence of tax deductions, the optimal tax rate for maximizing tax revenue in terms of labor income is below 45%, while for capital income, it is below 40%. In contrast, when tax deductions are present, tax rates exceeding 50% and 55% maximize tax revenue for labor and capital income, respectively. Furthermore, the elasticity of taxable income for both labor and capital remains relatively constant across scenarios, with a slightly higher value observed when deductions are considered. Regarding capital income, the elasticity consistently exceeds 1 due to the presence of varied capital deductions. In both cases, the elasticity exhibits a downward slope, gradually decreasing as the tax rate increases and approaching a value of 1. In contrast, the ETI associated with labor income remains below 37%, regardless of the presence or absence of deductions. Furthermore, under tax revenue elasticity, the rate of reaction to the tax rate for the labor force is almost uniform in low tax rates and has a downward trend with the increase of the tax rate in all three cases (considering and not considering deductions). But in the case of reductions in the labor force, the amount of reaction is higher than the other two cases. While the elasticity of tax income from capital gains due to capital depreciation deductions is always greater than 1 and is downward in all three cases and gradually decreases with the increase of the tax rate and approaches 1. Methodology In the current research, to understand the effects of tax exemptions and deductions in the economic system, an attempt has been made to analyze the effects of tax deductions on the government tax revenues and the elasticity of taxable income and tax elasticity, in a simple three-part dynamic general equilibrium model including households, firms and government, three special cases regarding the absence of tax deductions and social security premiums should be investigated. To evaluate and estimate the model, first the calibrated parameters in previous studies were collected and then the results were obtained through MATLAB software. Discussion and Conclusion One of the important results of this research is the changes in the government tax income and the reaction of individuals in the form of taxable income, caused by the consideration and non-consideration of deductions and tax exemptions on the household and corporate sectors. As it can be seen, tax revenues in the scenario of removing tax deductions are more than the other two scenarios, i.e. considering deductions, on the other hand, the elasticity of taxable income in the presence of tax deductions show a greater reaction than in the case of not considering tax deductions. Iran has been experiencing consecutive budget deficits over different periods. As a result of reduced oil revenues much greater attention has been drawn to a more efficient and effective taxing system. So, a substitution in the government revenue system can potentially deminish the over-dependence of the Iranian economy on oil revenues, which can lead to far reduced deficits both in the long and short term. In terms of deductions and exemptions as a factor affecting tax revenues, it can display a more realistic picture of an economy and take into account the existing economic realities. Therefore, the tax system should act in such a way that it moves in the direction of expanding the tax base. One of the solutions for this is realized through elimination of tax exemptions and deductions. It seems that such policies can prevent tax evasion, collecting more tax, and ultimately increase the motivation for work and activity and cause economic growth and prosperity